Ribosomal Protein S6 Hypofunction in Postmortem Human Brain Links mTORC1-Dependent Signaling and Schizophrenia - Ibarra-Lecue, Inés; Diez-Alarcia, Rebeca; Morentin, Benito; Meana, J. Javier; Callado, Luis F.; Urigüen, Leyre (Frontiers in Pharmacology, 2020)
The mechanistic target of rapamycin (also known as mammalian target of rapamycin) mTOR-dependent signaling pathway plays an important role in protein synthesis, cell growth and proliferation, and has been linked to the development of the central nervous system. Recent studies suggest that mTOR signaling pathway dysfunction could be involved in the etiopathogenesis of schizophrenia. The main goal of this study was to evaluate the status of mTOR signalling pathway in postmortem prefrontal cortex (PFC) samples of subjects with schizophrenia. For this purpose, we quantified the protein expression and phosphorylation status of the mTOR downstream effector ribosomal protein S6 as well as other pathway interactors such as Akt and GSK3β. Furthermore, we quantified the status of these proteins in the brain cortex of rats chronically treated with the antipsychotics haloperidol, clozapine or risperidone. We found a striking decrease in the expression of total S6 and in its active phosphorylated form phospho-S6(Ser235/236) in the brain of subjects with schizophrenia compared to matched controls. The chronic treatment with the antipsychotics haloperidol and clozapine affected both the expression of GSK3β and the activation of Akt (phospho-Akt (Ser473)) in rat brain cortex, while no changes were observed in S6 and phospho-S6 (Ser235/236) protein expression with any antipsychotic treatment. These findings provide further evidence for the involvement of the mTOR-dependent signaling pathway in schizophrenia and suggest that a hypofunctional S6 may have a role in the etiopathogenesis of this disorder.